Antibody prevalence to human enteric coronavirus-like particles and indications of antigenic differences between particles from different areas - Schnagl, R. D. (Arch Virol, 1986)
Antibody to human enteric coronavirus-like particles was detected in Australian Aborigines, but at lower levels or not at all in Europeans. There were indications of antigenic differences between particles from different areas. Support was provided for consideration of such particles as infectious agents.